2020
DOI: 10.7150/jca.46391
|View full text |Cite
|
Sign up to set email alerts
|

High serum Androgen and Insulin concentrations increase the tendency of Endometrial Carcinoma

Abstract: Purpose: The objective of the study was to evaluate the important role played by androgen and insulin in the development of endometrial carcinoma (EC), and their combined effect on EC risk. Methods: We enrolled 510 type I EC patients and 510 age-, time-, and nationality-matched subjects into this study. Metabolic and hormonal parameters of enrolled subjects were examined. Univariate and multivariate logistic regression analyses for EC and control subjects were performed. Type I EC risk was evaluated with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…PCOS and BMI ≥25 kg/m 2 were two independent risk factors that affect fertility-preserving treatment. This is consistent with studies showing that PCOS patients tend to show obesity, IR and higher testosterone levels, which are all thought to negatively affect fertility-preserving treatment outcome [ 7 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…PCOS and BMI ≥25 kg/m 2 were two independent risk factors that affect fertility-preserving treatment. This is consistent with studies showing that PCOS patients tend to show obesity, IR and higher testosterone levels, which are all thought to negatively affect fertility-preserving treatment outcome [ 7 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, numerous studies have also examined the potential role of androgens as risk factors for EC. In addition, most of them claimed to have found that elevated serum testosterone level increased EC risk (18)(19)(20)(21). It is tempting to speculate that AR is one of negative prognostic factors in EC.…”
Section: Discussionmentioning
confidence: 99%
“…Since it occurs mainly in adipose tissue, estrogen production will be increased in obese PCOS patients. Furthermore, unbalanced estrogen stimulation can lead to endometrial hyperplasia and endometrial cancer ( 230 ).…”
Section: Ovariesmentioning
confidence: 99%